Features of dielectric response in PMN-PT ferroelectric ceramics - Guerra, J. D. S.; Araujo, E. B. [UNESP]; Guarany, C. A. [UNESP]; Reis, R. N. [UNESP]; Lima, E. C. [UNESP] (Iop Publishing Ltd, 2008)
In this paper, electrical and structural properties were reported for pyrochlore free (1-x)[Pb(Mg1/3Nb2/3)O-3] - xPbTiO(3) (PMN-PT) (with 35 mol% PbTiO3) ceramics obtained from fine powders. Dielectric studies were focused on the investigation of the complex dielectric permittivity (epsilon '-i epsilon '') as a function of frequency and temperature. The effects of the dc applied electric field on dielectric response were also investigated. Results revealed a field dependence dielectric anomaly in the dielectric permittivity curves (epsilon(T)) in the low dc electric field region, which in turn prevails in the whole analysed frequency interval. To the best of our knowledge, these properties for the PMN-PT ceramic system have not been reported before as in this work. The results were analysed within the framework of the current models found in the literature.